Revitalizing Arabic Language Learning: The Role of Technology in Improving Language Proficiency - Rima Ajeng Rahmawati (Asalibuna, 2023)
The use of technology can create a more interactive atmosphere in Maharatul Qira'ah Al-Mutawassithah subject. The purpose of this research is to identify the role and forms of technology implementation in learning, as well as the format of technology-based learning evaluation. This study employs a qualitative approach with a case study conducted in the Intensive third semester of the Arabic Language Education Program, at STIT Darul Fattah Bandar Lampung. The research findings indicate that the lecturer has utilized technology in the teaching and learning process of Maharatul Qira'ah Al-Mutawassithah, including the delivery of subject materials, learning tools, and learning evaluation. Various applications and devices were employed, such as a laptop, projector, Microsoft PowerPoint, Mentimeter, WiFi, online learning platforms, YouTube, e-books, Quizizz, and digital portfolios. Based on the research findings, it is evident that the use of technology in the learning process significantly contributes to enhancing motivation and interaction during the course. As a result, the Mid-Semester evaluation revealed a remarkable improvement in learning outcomes compared to the Maharatul Qira'ah Al-Asasiyah course taught in the previous semester by the students.